Absence of measles viral genomic sequence in intestinal tissues from Crohn's disease by nested polymerase chain reaction. Issue 2 (February 1996) - Haga, Y; Funakoshi, O; Kuroe, K; Kanazawa, K; Nakajima, H; Saito, H; Murata, Y; Munakata, A; Yoshida, Y
Abstract : The aetiology of Crohn's disease remains unknown, although evidence for a viral cause has long been sought. Recent studies have shown inflammation of the submucosal microvascular endothelium and granulomata, and endothelial cell cytoplasmic inclusions, consistent with paramyxovirus, were identified by electron microscopy suggesting a persistent measles virus infection in Crohn's disease. Measles, mumps, and rubella viruses were tested for Crohn's disease by polymerase chain reaction (PCR). RNA was extracted from resected intestinal specimens from 15 patients with Crohn's disease, 14 with ulcerative colitis, and 14 controls without inflammatory bowel disease. This was used to perform nested PCR after reverse transcription (RT) of the RNA to cDNA with primer pairs directed against two regions in the genome of the measles virus and one region in the mumps and rubella viral genomes. Despite enhanced sensitivity of nested RT-PCR, measles, mumps, and rubella viral genomic sequences were not found in any intestinal specimen.